2021
DOI: 10.1177/10600280211006645
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Management of Eptifibatide-Induced Thrombocytopenia

Abstract: Background Eptifibatide is used in acute coronary syndromes to reversibly block platelet aggregation by inhibiting the platelet glycoprotein IIb/IIIa receptor. A serious adverse effect of eptifibatide is a profound drop in platelet count, termed eptifibatide-induced thrombocytopenia (EIT). Objective To provide insight into the types of complications and management of EIT. Methods Cases of EIT submitted to the Food and Drug Administration adverse event reporting system were evaluated. Data analyses included man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most patients develop minor bleeding, including petechiae or trivial bleeding from catheter sites. However, major bleeding, such as gastrointestinal bleeding or hematuria, has been reported, and some patients developed life-threatening bleeding necessitating further management [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients develop minor bleeding, including petechiae or trivial bleeding from catheter sites. However, major bleeding, such as gastrointestinal bleeding or hematuria, has been reported, and some patients developed life-threatening bleeding necessitating further management [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Masood et al reported on 57 cases of eptifibatide‐induced thrombocytopenia identified in the US Food and Drug Administration adverse reporting system. 44 The mean (±SD) nadir in 35 patients was 9000±19 000 platelets/μL. Bleeding symptoms were present in 57% of cases and included bleeding from the catheterization site (14%), petechial hemorrhages (14%), groin hematomas (7%), bleeding from infusion site (7%), gastrointestinal bleeding (3.6%), hemoptysis (3.6%), epistaxis (3.6%), and hematuria (3.6%).…”
Section: Gpi ‐Associated Thrombocytopeniamentioning
confidence: 99%
“…Treatment options for EIT include stopping the infusion, platelet transfusions (which may be inefficient because of the half-life of GPI), and fresh frozen plasma (used in major bleeding). Other treatment options include the use of corticosteroids (which are not effective) and intravenous immunoglobulin G (IVIG) [ 117 ].…”
Section: Eptifibatidementioning
confidence: 99%
“…Masood et al showed that out of 28 reported complications of EIT, 57% involved bleeding events. These included 14% catheterization site bleeding, 14% petechial hemorrhage, 7% groin hematoma, 7% infusion site bleeding, 3.6% gastrointestinal bleeding, 3.6% hemoptysis, 3.6% epistaxis, and 3.6% hematuria [ 117 ]. Diffuse alveolar hemorrhage (DAH) is another important but often underappreciated form of eptifibatide-related bleeding.…”
Section: Eptifibatidementioning
confidence: 99%
See 1 more Smart Citation